New Aspects of the Epigenetics of Pancreatic Carcinogenesis - Murat Toruner; Martin E. Fernandez-Zapico; Christopher L. Pin (Epigenomes, 2020)
Pancreatic cancer remains among the deadliest forms of cancer with a 5 year survival rate less than 10%. With increasing numbers being observed, there is an urgent need to elucidate the pathogenesis of pancreatic cancer. While both contribute to disease progression, neither genetic nor environmental factors completely explain susceptibility or pathogenesis. Defining the links between genetic and environmental events represents an opportunity to understand the pathogenesis of pancreatic cancer. Epigenetics, the study of mitotically heritable changes in genome function without a change in nucleotide sequence, is an emerging field of research in pancreatic cancer. The main epigenetic mechanisms include DNA methylation, histone modifications and RNA interference, all of which are altered by changes to the environment. Epigenetic mechanisms are being investigated to clarify the underlying pathogenesis of pancreatic cancer including an increasing number of studies examining the role as possible diagnostic and prognostic biomarkers. These mechanisms also provide targets for promising new therapeutic approaches for this devastating malignancy.